Development of a Modified BSPT-Based Shooting Skill Test Instrument for Basketball Players Aged 16–18 Years - Fina Luluk Chumaidah; Himawan Wismanadi; Achmad Widodo; Irmantara Subagio (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This study aimed to develop and evaluate the feasibility of a basketball shooting skill test instrument specifically designed for male players aged 16–18 years, based on a modified Basketball Skill Performance Test (BSPT) framework. The primary objective was to produce a standardized, content-valid, and practically applicable assessment tool capable of objectively measuring three distinct shooting competencies: free throw, three-point shooting, and right–left lay-up execution. Materials and methods. A developmental research design was adopted, guided by the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Content validity was assessed through a Focus Group Discussion (FGD) involving two accredited sport science experts and one licensed basketball coach. The instrument was subjected to a small-scale field trial (n = 10) and subsequently refined prior to a large-scale field test (n = 30), involving male basketball club players aged 16–18 years selected via purposive sampling. Each test component was administered under standardized conditions using consistent equipment. Data were analyzed using descriptive statistics, encompassing mean (M), standard deviation (SD), minimum and maximum scores, as well as frequency and percentage distributions based on a five-scale performance rubric. Results. The free throw test yielded a moderate mean performance score (M = 5.43; SD = 1.96), indicating stable shooting consistency with moderate variability. The three-point shooting test produced the lowest mean score (M = 2.50; SD = 2.39), reflecting significantly greater task difficulty and wider inter-individual variability in long-range shooting accuracy. The right–left lay-up test demonstrated the highest mean score (M = 7.80; SD = 1.83), reflecting well-developed bilateral finishing skills. Score distributions across all components were free from floor and ceiling effects, confirming adequate discriminative ability at each performance level. Conclusions. The developed basketball shooting skill test instrument is content-valid, practically feasible, and contextually appropriate for the systematic evaluation of shooting skills in basketball players aged 16–18 years. The instrument provides balanced difficulty gradients across shooting components, enabling objective, multi-dimensional performance assessment in both training and competitive development settings. Its adoption is recommended for coaches and sport science practitioners engaged in youth basketball athlete monitoring and development.